Esophageal lung - A rare bronchopulmonary foregut malformation - S.V. Parelkar; B.V. Sanghvi; S.H. Patil; S.S. Mhaskar; G. Munghate; N.S. Sisodiya; P. Tiwari; A.A. Pawar; R.S. Shah; S.N. Oak (Elsevier, 2014)
Esophageal lung is a rare variety of communicating bronchopulmonary foregut malformation characterized by a fistula between an isolated portion of respiratory tissue and esophagus or stomach. It may involve the entire lung or one of the pulmonary lobes. Only 20 cases have been reviewed in 2011. Fifty percent of cases are associated with a tracheoesophageal fistula. We report a case of a 6 month old girl who was previously operated for TEF repair, with esophageal lobe which was successfully excised. The relevant literature is reviewed.